Intervensi Oral Neuromuscular Training untuk Pasien Lansia dengan Disfagia Pasca Stroke - Agnes Dewi Astuti; Bernadetta Germia Aridamayanti (FORIKES, 2021)
Background: Dysphagia is one of the most common complications in patients suffering from acute stroke. Dysphagia in acute and chronic stroke patients can be caused by various factors. Giving therapy and exercises during the rehabilitation period will accelerate recovery in dysphagia patients, especially the elderly. Objective: To describe the various forms of neuromucular oral exercise intervention in elderly patients suffering from poststroke dysphagia. Methods: The databases used in this study are Scopus, Proquest and Science Direct, limited to publications for the last 5 years from 2017 to 2021, full text articles and in English. The keywords used in the search were “dysphagia intervention” AND “elderly stroke” AND “oral neuromuscular training”. This systematic review uses 7 articles that match the inclusion criteria. Results: There are 7 exercise interventions that can stimulate motor muscles in the pharynx of patients suffering from dysphagia. These interventions include oral neuromuscular training, orofacial sensory-vibration stimulation, Mendelsohn's Maneuvers, oro-esophageal tube training, acupuncture, He's Santong Needling Method and Surface Electromyographic Biofeedback and the Effortful Swallow Exercise. Each exercise or therapy that is given has its own advantages and works in accordance with the stimulation of neuroplasticity in various areas of the brain so as to accelerate the increase in oxygen, glucosan and metabolites which will eventually stimulate the movement to return to swallowing and speaking normally. Conclusion: Various kinds of therapy in the form of exercise can be given to post-stroke dysphagia patients, especially in elderly patients. These interventions provide concrete evidence in stimulation of the motor pharyngeal muscles so that they can help speed up recovery in the rehabilitation phase. Suggestion: The interventions described in this systematic review are deemed necessary to be applied in hospitals in Indonesia.Keywords: dysphagia intervention; elderly stroke; oral neuromuscular trainingABSTRAKLatar belakang: Disfagia merupakan salah satu komplikasi tersering pada pada pasien yang menderita stroke akut. Disfagia pada pasien stroke akut dan kronis dapat disebabkan oleh berbagai macam faktor. Pemberian terapi dan latihan pada masa rehabilitasi akan mempercepat pemulihan pada pasien disfagia terutama lansia. Tujuan: Untuk menjabarkan berbagai bentuk intervensi latihan oral neuromucular pada pasien lansia yang menderita disfagia post stroke. Metode: Database yang digunakan dalam penelitian ini adalah Scopus, Proquest dan Science Direct terbatas untuk publikasi 5 tahun terakhir dari 2017 hingga 2021, full text article dan berbahasa Inggris. kata kunci yang digunakan pada pencarian artikel adalah “dysphagia intervention” AND “elderly stroke” AND “oral neuromuscular training”. Systematic review ini menggunakan 7 artikel yang sesuai dengan kriteria inklusi. Hasil: Terdapat 7 intervensi latihan yang dapat menstrimulasi otot motorik pada faring pasien yang menderita disfagia. Intervensi tersebut antara lain adalah oral neuromuscular training, orofacial sensory-vibration stimulation, Manuver Mendelsohn, oro-esophageal tube training, acupuncture, He’s Santong Needling Method dan Surface Electromyographic Biofeedback and the Effortful Swallow Exercise. Setiap latihan atau terapi yang diberikan memiliki keunggulannya masing masing dan bekerja sesuai dengan rangsanagan dari neuroplastisitas pada berbagai area otak sehingga memperlancar peningkatan oksigen, glukosan dan metabolit yang akhirnya akan menstimulasi gerakan untuk kembali dapat menelan dan berbicara secara normal. Simpulan: Berbagai macam terapi dalam bentuk latihan yang dapat diberikan pada pasien disfagia post stroke terutama pada pasien lansia. Intervensi-intervensi ini memberikan bukti yang konkret dalam stimulasi otot motorik faring sehingga dapat membantu mempercepat pemulihan pada fase rehabilitasi. Saran: Intervensi yang dijabarkan pada systematic review ini dipandang perlu untuk diterapkan di rumah sakit yang ada di Indonesia.Kata kunci: dysphagia intervention; elderly stroke; oral neuromuscular training